2008
DOI: 10.1172/jci33569
|View full text |Cite
|
Sign up to set email alerts
|

Hip1r is expressed in gastric parietal cells and is required for tubulovesicle formation and cell survival in mice

Abstract: Huntingtin interacting protein 1 related (Hip1r) is an F-actin-and clathrin-binding protein involved in vesicular trafficking. In this study, we demonstrate that Hip1r is abundantly expressed in the gastric parietal cell, predominantly localizing with F-actin to canalicular membranes. Hip1r may provide a critical function in vivo, as demonstrated by extensive changes to parietal cells and the gastric epithelium in Hip1r-deficient mice. Electron microscopy revealed abnormal apical canalicular membranes and loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 53 publications
3
55
2
Order By: Relevance
“…Interestingly, expression levels of Hip1R (18), EHD1, and EHD2 (19-21) were higher in the stomach than in the brain. Hip1R, a protein that shares partial domain similarity with epsin (it contains an N-terminal ENTH-like domain) and that links clathrin coats to the actin cytoskeleton, was previously shown to be highly concentrated at apical canaliculi of gastric parietal cells and to be implicated in H/K ATPase endocytosis (18,22). Furthermore, recent studies in Dictyostelium have suggested a strong functional partnership between epsin and Hip1R at the interface between clathrin-mediated endocytosis and actin (23).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, expression levels of Hip1R (18), EHD1, and EHD2 (19-21) were higher in the stomach than in the brain. Hip1R, a protein that shares partial domain similarity with epsin (it contains an N-terminal ENTH-like domain) and that links clathrin coats to the actin cytoskeleton, was previously shown to be highly concentrated at apical canaliculi of gastric parietal cells and to be implicated in H/K ATPase endocytosis (18,22). Furthermore, recent studies in Dictyostelium have suggested a strong functional partnership between epsin and Hip1R at the interface between clathrin-mediated endocytosis and actin (23).…”
Section: Resultsmentioning
confidence: 99%
“…Fused secretory membranes with a lack of tubulovesicles are a hallmark of the altered ultrastructure of these PCs (22), similar to what we observed in Kir4.1 ÏȘ/ÏȘ PCs. Second, Jain et al (24) recently described the Hip1r-deficient mouse, which also displayed similar changes in PC ultrastructure compared with Kir4.1 ÏȘ/ÏȘ mice, with fully elaborated secretory membranes in the absence of an acid secretory agonist and a lack of tubulovesicles. Interestingly, [ 14 C]aminopyrine accumulation as a measure of acid formation in isolated gastric glands was increased in the Hip1r mouse, whereas overall acid output into the lumina of the stomachs of anesthetized mice was decreased.…”
Section: Kir41 Channels In Gastric Acid Secretionmentioning
confidence: 90%
“…Several studies have demonstrated that the PCs play an important role in the process of differentiation and development of other cell lineages in the gastric mucosa, as loss of mature PCs alters the normal differentiation program of the gastric epithelium and causes different types of mucosal cell remodeling (Li et al 1995(Li et al , 1996Canfield et al 1996;Lopez-Diaz et al 2006;Jain et al 2008). In our previous investigations we reported that inhibition of BMP signaling in the stomach leads to a marked decrease in the number of PCs and to the appearance of aberrant lineages that express markers of both zymogenic and mucus neck cell differentiation (Shinohara et al 2010;Takabayashi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that in mice, the ZCs differentiate from pluripotent stem cells through a multistep process that involves the progressive transition of mucus neck cells into fully differentiated ZCs (Nam et al 2010). It has been also shown that this process might be regulated by parietal-cell secreted factors as loss of PCs leads to alterations in the normal process of ZC maturation and differentiation (Li et al 1995(Li et al , 1996Canfield et al 1996;Lopez-Diaz et al 2006;Jain et al 2008;Shinohara et al 2010;Takabayashi et al 2014). It is therefore possible that the abnormalities in ZC differentiation that we observed in the NogTG;GasKO mice might be mostly secondary to the presence of aberrant, poorly differentiated PCs, although we cannot completely exclude that both gastrin and the BMPs might have cooperative, direct effects on the ZCs.…”
Section: Discussionmentioning
confidence: 99%